Unraveling the spatiotemporal trends and source attribution of polycyclic aromatic hydrocarbons and oxygenated derivatives in Guangzhou agricultural ditch sediment - Shaomin Li; Weisong Chen; Yichen Liu; Haoyu Wang; Yongtao Li; Zhen Zhang; Xingjian Yang (Ecotoxicology and Environmental Safety)
Oxygenated polycyclic aromatic hydrocarbons (OPAHs) have garnered significant scientific attention due to their heightened toxicity and mobility compared to their parent PAHs. This study investigated the occurrence of 11 OPAHs and 16 PAHs within agricultural ditch sediment of Guangzhou City, China. The ΣPAH and ΣOPAH concentrations ranged from 63.8–3955 ng/g and 16.5–522 ng/g, respectively. Notably, concentrations were elevated during the rainy season, attributed to intensified atmospheric deposition and surface runoff during the rainy season. Spatially, Pearson correlation and path analysis disclosed a linkage between OPAHs and high-molecular-weight PAHs and adjacent agricultural practices, whereas low-molecular-weight PAHs were associated with human and industrial operations. This disparity was linked to the restricted mobility of high-molecular-weight PAHs, rendering them particularly susceptible to proximal sources. Diagnostic ratios and principal component analysis-multiple linear regression (PCA-MLR) implicated fossil fuel combustion and vehicle emissions as major contributor to the sedimentary OPAHs and PAHs. Further correlations between estimated source contributions and water quality, strengthened by spatial interpolation, clearly identified agricultural activities, and atmospheric deposition associated with traffic emissions and fossil fuel combustion as primary contributor to sedimentary OPAHs and PAHs. Secondary sources encompassed coal combustion, road runoff, and wastewater from both industrial and shipping activities. The risk quotients (RQs) for PAH and OPAH mixtures indicated moderate to high ecological hazards. This study demonstrated the importance of employing the integrated approach, combining PCA-MLR, diagnostic ratios, and correlation of source contributions with water quality in precisely delineating the origins of OPAHs and PAHs in agricultural ditch sediment.